Sensitivity Analysis for Effect of Changes in Input Data on Hydrological Parameters and Water Balance Components in the Catchment Area of Hungarian Lowland - Tran Hop Quang (Sciendo, 2021)
Extreme weather and climate changes are emerging more frequently in Central Europe, Hungary, and in the near future the increase in prolonged droughts, high-intensity precipitation events and the temporal variations of precipitation are expected, which may increase the magnitude of local water damages (OVF, 2016). As a result of climate change, these extreme weather events will be more frequent, however it is difficult to predict them, as until now insufficient amount of observations are available on smaller watercourses and on refined territorial water balances. For the future assessment of the environmental and economic impacts of climate change, it is essential to explore the integrated relationship of evapotranspiration, runoff, infiltration, surface and subsurface waters, and other hydrological processes, which can fundamentally describe regionally the water management conditions.